Practice-Led IP Development for Visual Narrative Education: The Sukawali Village Mangrove Mascot - Sella Putri Arby; Yohanes Merci Widiastomo; Cheryl Claire (ULTIMART Jurnal Komunikasi Visual, 2026)
This study documents the practice-led development of “Mangu,” a locally designed intellectual property (IP) representing a mangrove seedling, and its accompanying children’s storybook “Si Kecil Mangu” (Little Mangu), created as an educational visual narrative for children aged 6–7 years in Sukawali Village, Pakuhaji District, Tangerang Regency. Sukawali Village faces significant environmental and social challenges, including coastal abrasion, mangrove destruction, and limited access to educational media for children. Through collaboration with the Kampung Bahari Nusantara (KBN) community and Rumah Pintar volunteers, this research employs a qualitative and practice-led research approach to document the full IP creation process — from character design and social media audience testing to the production of a finalized storybook grounded in Dual Coding Theory, Visual Literacy Theory, and Narrative Transportation Theory. The findings demonstrate that theory-informed visual narrative design produces educational media that is both locally grounded and academically rigorous. Beyond its immediate educational function, “Mangu” offers a replicable model for how mascot-based IP can be developed through participatory, practice-led processes to support community-based environmental education in coastal conservation contexts.